Aspek Hukum Penyederhanaan Perizinan Badan Usaha di Bidang Lingkungan Hidup dalam Undang-Undang Cipta Kerja - Fitri Yanni Dewi Siregar (Jurnal Ilmiah Penegakan Hukum, 2020)
This study aims to determine the concept of business licensing in the environmental sector contained in Law Number 32 of 2009 concerning Environmental Protection and Management (UUPPLH) using a permit-based approach (license approach) which will be converted into a standard application and a risk line (Risk). -Based Approach / RBA) in the Job Creation Law, this means that later the granting of permits will be carried out by the central government based on the calculation of the value of the level of danger and the value of potential hazards to aspects of health, safety, environment and/or resource utilization. The research method used is a normative juridical approach based on primary legal materials. This study uses an approach: statute approach, conceptual approach, and case approach. The technique of tracing legal materials uses document study techniques, and the analysis of studies uses qualitative analysis.